Aneurysm of Left Atrial Appendage: Report of two repaired cases - M, Sharifuzzaman; MAK, Azad; Biswas, Prodip K; A, Momen; NAH, Choudhury; K, Shahreen; A, Biswas; S, Sarmin (Bangladesh Heart Journal, 2021)
Left atrial appendage aneurysm is a rare heart defect; Most often diagnosed incidentally but may be potentially hazardous when presented with a systemic embolization or arrhythmia. So early diagnosis and treatment is indicated. We have successfully operated two cases of left atrial aneurysm in recent past and sharing our experiences through this case reports. Bangladesh Heart Journal 2021; 36(2): 158-163